Total Factor Productivity of Thai Banks in 2007 – 2010. An Application of DEA and Malmquist Index - Ngo, Dang Thanh (2016)
This research employs the Data Envelopment Analysis and Malmquist index approaches to evaluate the efficiency and Total Factor Productivity changes of Thai banking system in the period of 2007-2010 using panel data of 27 major banks in Thailand. This paper shows that the global crisis had a late effect on Thai banks as the TFP only dropped in 2010.